Start-up firms and corporate culture: Evidence from advertised corporate culture - LEE, Jungho (Institutional Knowledge at Singapore Management University, 2022)
I document advertised corporate culture among start-up firms from an online job board. Two corporate-culture types emerge, one that concerns the well-being of em- ployees (worker-centered culture) and another that emphasizes other values, such as cus- tomers, firms, and markets (firm-centered culture). The worker-centered culture attracts 20% more applications than the other culture type. Firms advertising the worker-centered culture exploit worker preference by paying 5% lower salaries than measurably similar jobs. Using a standard model of business creation, I show financially constrained start- ups are incentivized to advocate popular culture, even though doing so is not optimal without financial constraints.